Relationship between Hard Skills and Soft Skills Towards Employee Performance at Crew Restauran KFC Medan (The Indonesian Journal of Business Administration, 2021)
Industry 4.0 is about competitiveness and innovation. Organizations need to adapt their capabilities to handle new challenges. Besides change management, a sequential concept, design thinking is an iterative approach linking creative and analytical methods. The goal is to foster new ideas and concepts and increase organizations'; innovative power and competitiveness, and currently, the COVID-19 attack has shocked the world. The COVID-19 pandemic has surprised many organizations. This situation will affect work that changes organizational culture, such as work from home (WFH) instructions for employees, virtual organization control, and supervision by leaders previously only performed by large organizations. One of the companies that have a significant impact due to COVID-19 is PT. Fast Food Indonesia Tbk, which is the sole owner of the KFC franchise in Indonesia, was founded by Gelael in 1978 as the first party to acquire a KFC franchise for Indonesia. The company started operation in October 1979 at Jalan Melawai, Jakarta. This foreign Quick Service Restaurant's success was then followed by restaurants in major cities in Indonesia, which is Medan. While facing COVID-19, that happens in the world, other outlets of PT. Fast Food Indonesia, especially in Medan, has a goal to be achieved. The goal is to make KFC stable as before. This goal will be achieved through employee commitment and good performance. Lack of employee performance happened from any causes. Therefore, this research intended to find out the relationship between skills and employee performance during COVID-19 in term of facing Industri 4.0 Keywords: Hard Skills, Soft Skills, Employee Performance, COVID-19, Industry 4.0, Multilinear Regression